A parser for simple Malayalam sentences - Jasine Babu
A\parser is a program that checks whether the given string is syntactically correct according to the grammar specification. The importance of syntax analysersfor natural languages is increasing day by day, as we are facing with the growing needs for machine understanding of natural languages, language to language translation etc. Here, the objective is to make a grammar checker for parsing simple Malayalam sentences. The user will be giving the sentence to be parsed using English script. If the sentence is syntactically correct, the parser will output a correct parse trace. If the sentence is not well formed, the parser will give a negative answer. The emphasis is given to the grammar so that the dictionary contains only limited entries. However, there is provision for the user to expand the lexicon.